PENGARUH TEKANAN KETAATAN, SENIORITAS AUDITOR DAN TEKANAN ANGGARAN WAKTU TERHADAP AUDIT JUDGMENT - Agustini, Ni Ketut Riski; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi, 2016)
Auditor is a profession that one of the duties carry out an audit of the financial statements, to carry out the task required an audit judgment. Audit judgment giving effect to the final conclusion. Performance audit the auditor in making the judgment is influenced by various factors. The purpose of this study was to examine the effect of adherence pressure, seniority auditor and time budget pressure on audit judgment. This study uses primary data were collected using a questionnaire as an instrument of data collection techniques that spread to the respondent. Respondents are auditors who worked on KAP in Bali listed on the Indonesian Institute of Certified Public Accountants. The sampling method using saturated sample. Number of questionnaires distributed as much as 87 questionnaires, while that may be used as further analysis of 50 questionnaires. The analysis technique used multiple linear regression analysis. Based on the analysis found that that pressure obedience and time budget pressure on audit judgment, whereas seniority auditor's judgment does not affect the audit.
Keywords: Audit Judgment, Pressure Obedience, Seniority Auditor, Time Budget Pressure